Powder metallurgy of titanium – past, present, and future. (3rd October 2018) - Fang, Zhigang Zak; Paramore, James D.; Sun, Pei; Chandran, K. S. Ravi; Zhang, Ying; Xia, Yang; Cao, Fei; Koopman, Mark; Free, Michael
ABSTRACT: Powder metallurgy (PM) of titanium is a potentially cost-effective alternative to conventional wrought titanium. This article examines both traditional and emerging technologies, including the production of powder, and the sintering, microstructure, and mechanical properties of PM Ti. The production methods of powder are classified into two categories: (1) powder that is produced as the product of extractive metallurgy processes, and (2) powder that is made from Ti sponge, ingot, mill products, or scrap. A new hydrogen-assisted magnesium reduction (HAMR) process is also discussed. The mechanical properties of Ti-6Al-4V produced using various PM processes are analyzed based on their dependence on unique microstructural features, oxygen content, porosity, and grain size. In particular, the fatigue properties of PM Ti-6Al-4V are examined as functions of microstructure. A hydrogen-enabled approach for microstructural engineering that can be used to produce PM Ti with wrought-like microstructure and properties is also presented. Abbreviations: AM: additive manufacturing; ARC: Albany Research Center; BE: blended elemental; BUS: broken-up structure; CCGA: close-coupled gas atomisation; CHIP: CIP-sinter-HIP; CIP: cold isostatic pressing; CP-Ti: commercially pure Ti; DRTS: direct reduction of Ti-slag; CSIR: Council for Scientific and Industrial Research (South Africa); CSIRO: Commonwealth Scientific and Industrial Research Organization (Australia); EIGA: electrode induction gas atomisation; EMR: electronically mediated reduction; FFC: Fray, Farthing, and Chen; GA: gas atomisation; GIF: gaseous isostatic forging; GSD: granulation-sintering-deoxygenation; HAMR: hydrogen-assisted magnesium reduction; HDH: hydride–dehydride; HIP: hot isostatic pressing; HSPT: hydrogen sintering and phase transformation; MA: master alloy; MER: Materials & Electrochemical Research Corporation (US); MHR: metal hydride reduction; MIM: metal injection molding; OM: optical microscope; OS: Ono and Suzuki; PA: pre-alloyed; P/C: performance to cost ratio; PIF: pneumatic isostatic forging; PM: powder metallurgy; PREP: plasma rotating electrode process; PP: post-processing; PS: press and sinter; QIT: Quebec Iron & Titane, Inc. (Canada); SEM: scanning electron microscope; SPS: spark plasma sintering; SOM: solid oxide membrane; THP: thermohydrogen processing; TMP: thermomechanical processing; UFG: ultrafine grain; UGS: upgraded titanium slag; UTS: ultimate tensile strength; USTB: University of Science and Technology Beijing (China); VA: vacuum atomisation; VHP: vacuum hot pressing; WP: wrought process; YS: yield strength